2020
DOI: 10.1108/jarhe-04-2020-0109
|View full text |Cite
|
Sign up to set email alerts
|

Predicting entrepreneurial opportunity recognition in higher education: a case from Iran

Abstract: PurposeAlthough extensive governmental efforts have taken place to promote entrepreneurship in Iran, based on global entrepreneurship monitor report, the rate of perceived opportunities among young people, especially those with university education, has dropped. Since the perceived entrepreneurial opportunities are the first and most important step in the entrepreneurship process, this study identified the factors affecting the entrepreneurial opportunity recognition in Iranian higher education.Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…As EA is at the center of the growth of agricultural entrepreneurship, it is important to investigate how the social and human resources of agricultural students influence their EA. Considering that the results of previous studies indicate the weakness of entrepreneurial activities in Iran (such as Chavoushi et al, 2021;Naderi et al, 2020;Karimi et al, 2015Karimi et al, , 2016bBosma andKelley, 2018/ 2019) and according to the results of the study by Mehdizadeh et al (2021), agricultural students of Ilam province have low EA. Furthermore, Ilam province, with its appropriate characteristics for the development of the agricultural sector in terms of regional and local capacities, can play an important role in the development of Iran's economy as an important agricultural hub in the future.…”
Section: Sustainable Agribusiness Developmentmentioning
confidence: 92%
“…As EA is at the center of the growth of agricultural entrepreneurship, it is important to investigate how the social and human resources of agricultural students influence their EA. Considering that the results of previous studies indicate the weakness of entrepreneurial activities in Iran (such as Chavoushi et al, 2021;Naderi et al, 2020;Karimi et al, 2015Karimi et al, , 2016bBosma andKelley, 2018/ 2019) and according to the results of the study by Mehdizadeh et al (2021), agricultural students of Ilam province have low EA. Furthermore, Ilam province, with its appropriate characteristics for the development of the agricultural sector in terms of regional and local capacities, can play an important role in the development of Iran's economy as an important agricultural hub in the future.…”
Section: Sustainable Agribusiness Developmentmentioning
confidence: 92%
“…46 conducted a quantitative analysis to demonstrate that students have the ability to recognize opportunities and the opportunity recognition process may be influenced by their traits, and social capital. Similarly, 47 found that senior level undergraduate students have a moderate level of finding opportunities and their abilities were influenced by their alertness and social capital.…”
Section: Opportunity Recognitionmentioning
confidence: 94%